PEMBENTUKAN KARAKTER UNGGUL DAN NASIONALIS PADA ANAK USIA DINI MELALUI SEKAR RARE - Seriadi, Si Luh Nyoman (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2017)
Character Building must be started in early age. Hence, the earlier children were acquainted with noble value, then their basic character would be stronger in the future. Furthermore, to build such a noble character towards the children itself, their environment should reflect good and positive things vice versa. One of the methods to build their character is through introducing song for children with positive values as well as moral messages.Moral values inserted in the lyrics of children’s songs are intended to educate the development of a child’s psychology.The dolanan song or commonly known as Gending rare in Balinese culture provide such positive benefit in order to build character. Whereas, Gending Rare comprise educational values such as honesty, Concord, history, culture, nationalism, and respect other people, including other several positive things. The example of Gending Rare which will be explained in this paper is gending rare entitled “mare bangun” and “merahputih”.